2019
DOI: 10.1016/j.alcohol.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the 2018 Alcohol and Immunology Research Interest Group (AIRIG) meeting

Abstract: On November 21, 2014 the 19th annual Alcohol and Immunology Research Interest Group (AIRIG) meeting was held at Loyola University Chicago Health Sciences Campus in Maywood, Illinois. The meeting focused broadly on inflammatory cell signaling responses in the context of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In turn, whereas alcohol is a well-known pro-oxidant agent [77], the modulation of inflammatory and oxidative biomarkers largely depends on the type of beverage consumed [76,78,79], and part of these effects may be mediated by non-alcoholic components of alcoholic beverages as is further discussed. Again, heavy drinking increases the concentration of inflammatory and oxidative parameters [80][81][82] leading to CV morbidity.…”
Section: Intermediate Biomarkers Of Cardiovascular Diseasementioning
confidence: 99%
“…In turn, whereas alcohol is a well-known pro-oxidant agent [77], the modulation of inflammatory and oxidative biomarkers largely depends on the type of beverage consumed [76,78,79], and part of these effects may be mediated by non-alcoholic components of alcoholic beverages as is further discussed. Again, heavy drinking increases the concentration of inflammatory and oxidative parameters [80][81][82] leading to CV morbidity.…”
Section: Intermediate Biomarkers Of Cardiovascular Diseasementioning
confidence: 99%
“…Omega-3 and omega-6 fatty acids are known for their modulating effects on inflammatory processes (27) and a dietary intake low in omega-6:omega-3-ratio of ideally ≤2:1 is associated with a reduced proinflammatory cytokine release (28). Furthermore, smoking (29), alcohol consumption (30), and medication use (31) can affect the inflammatory status. However, the number of smokers was low and alcohol intake between groups was comparable (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chronic alcohol abuse has been correlated with high iron concentrations in the skin [54]. Studies in aldehyde dehydrogenase 2 gene knockout mice or humans with dysfunctional alcohol metabolism have also shown that alcohol can cause increased skin pigmentation, although the downstream mechanisms are unclear [55]. Alcohol disrupts the iron-induced increase in hepatic hepcidin transcription, thereby impeding intestinal iron absorption and the release of iron from macrophages.…”
Section: Diets and Lifestyle On Ironmentioning
confidence: 99%